The Ju'alah Contract in The Digital Age: A Sharia Law Analysis of Commission in Shopee's Affiliate Program - Muhammad Dayyan; Safrina; Ismail Fahmi Arrauf Nasution (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
The purpose of this study is to understand commission setting in business practices through Shopee Affiliate, analyze the legal relationship (rights and obligations) between affiliates and Shopee from the perspective of Sharia Economic Law, and to see the legal implications of determining commissions for parties in the Shopee affiliate program based on the muamalah agreement. With a qualitative approach, the primary data for this research was obtained by interviewing 6 (six) informants. Then analyzed using secondary data in the form of primary legal material from the Electronic Information and Transaction Law (UU ITE) as well as Minister of Trade Regulations and secondary legal material from Ulama fatwas. The results of this research reveal that the mechanism for implementing the Shopee Affiliate program is quite easy via smartphone. The legal relationship that occurs between Shopee and affiliates seen in the ITE Law is called a partnership relationship. Meanwhile, seen from the perspective of Sharia Economic Law, it shows that the legal relationship is in the ju'alah contract where Shopee as the company gives rewards to affiliates after successfully carrying out their work. The implication of the legal provisions for shopee affiliate business activities is that it is permissible or permitted to be done because it brings benefit to society and even becomes an opportunity to create added economic value from smartphone devices.